1891 Mich. Pub. Acts 408– 09, No. 257, § 15 - (:unkn) unknown (General Publisher, 1891)
Prohibited the carrying of a concealed pistol, revolver, Bowie knife, dirk, slungshot, billie, sandbag, false knuckles, or other dangerous weapon. Also prohibited lurking or being concealed with the intent to injure a person or property, or threatening to beat or kill a person or property. Punishable by fine up to $100 and the costs of prosecution, and in default of payment, imprisonment.
Note: California failed to mention that this law only applied in the County of Saginaw, not the whole state of Michigan
--
Keywords: CARRY - CONCEALED